A Process for Usability Testing of Lifesaving Equipment. (September 2016) - Porter, William; Kosmoski, Carin; Fernando, Rohan
Usability for any product, and especially for a lifesaving device, is critical in that the users will be interacting with the device in a highly stressful and complex environment. This study examined self- contained breathing apparatus (SCBAs) and conducted a usability assessment of these SCBAs with refill stations as it pertains to mine escape. Data was collected examining three usability topic areas (effectiveness, efficiency, and satisfaction) and eight constructs within these topic areas (completeness, accuracy, time requirements, overall satisfaction, discomfort, ease of use, system performance, and user preference). This paper documents the usability framework adopted and the methodology used to answer the research questions of the study and includes sample results and discussion. The methodology presented can be modified and used to test other lifesaving technologies to compare the usability of the devices and to estimate the ability of the devices to function as expected in a lifesaving situation.